SIMBOLISME NYUH MADAN DALAM RITUS HINDU DI BALI: Telaah Ontologis dan Kosmologis - Ida Bagus Putu Eka Suadnyana; Komang Heriyanti; I Nyoman Buda Asmara Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Nyuh Madan is a fundamental component in various Hindu rituals in Bali, serving not only as a ritualistic object but also as a profound symbolic medium. This article explores the ontological and cosmological dimensions of Nyuh Madan within the framework of Balinese Hindu philosophy. Employing a symbolic hermeneutic approach and reflective analysis of sacred texts and local ritual practices, this study reveals that the physical structure of Nyuh Madan represents key ontological concepts and the cosmological order. Its components—outer husk, coir, shell, water, and the eye of the coconut—symbolize the Panca Mahabhuta elements and the Tri Loka hierarchy, illustrating the interconnectedness between the macrocosm and the microcosm. The symbolism of Nyuh Madan affirms its role not merely as a ritual offering but as a spiritual conduit bridging the human and transcendent realms. Hence, a deeper appreciation of this symbol reinforces the unity of ritual, cosmological awareness, and dharmic values in Balinese Hindu life.